2020
DOI: 10.3390/ijerph17207689
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Firefighter Physical Fitness and Special Ability Performance: Predictive Research Based on Machine Learning Algorithms

Abstract: Firefighters require a high level of physical fitness to meet the demands of their job. The correlations and contributions of individual physical health parameters to the tasks of firefighting would enable firefighters to focus on the effects of specific physical conditions during their physical training programs. Therefore, the purpose of the present study was to identify the relationships between various physical health parameters (weight, maximum oxygen uptake, body fat percentage, upper body muscular power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
(64 reference statements)
0
16
0
4
Order By: Relevance
“…In addition, a high resting heart rate as correlated with poorer occupational performance (r � 0.36, p < 0.01). ese results were supported by two studies which reported that high BF% was associated with poor performance in the physical ability tests [63], and that aging and fat mass were significant predictors of work inefficiency in firefighters [64].…”
Section: Cardiovascular Disease Risk Factors and Occupationalmentioning
confidence: 67%
See 3 more Smart Citations
“…In addition, a high resting heart rate as correlated with poorer occupational performance (r � 0.36, p < 0.01). ese results were supported by two studies which reported that high BF% was associated with poor performance in the physical ability tests [63], and that aging and fat mass were significant predictors of work inefficiency in firefighters [64].…”
Section: Cardiovascular Disease Risk Factors and Occupationalmentioning
confidence: 67%
“…Poor body composition was significantly related to slower performance time on the simulation. Similarly, Xu et al [ 63 ] reported that poor body composition (higher BF%) was associated with poor performance on the work ability test in 20 full-time Chinese firefighters. Superior cardiorespiratory fitness, and upper and lower body muscular power, was inversely related to the completion times in the work ability test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original data matrix X, Y will be normalized to facilitate the expression of the corresponding data by the formula in the subsequent operation while reducing the error between data volumes, and the corresponding matrix will be obtained after processing. The E NK is the corresponding matrix for X NK and F NJ is the corresponding matrix for Y NJ for repeated iterative operations (Xu et al, 2020).…”
Section: Partial Least Squares Regression Methodsmentioning
confidence: 99%